Early Recurrent Hemorrhage in Submacular Hemorrhage Secondary to Type 3 Neovascularization or Retinal Angiomatous Proliferation: Incidence and Influence on Visual Prognosis. (18th August 2018) - Kim, Jae Hui; Chang, Young Suk; Kim, Jong Woo; Kim, Chul Gu; Lee, Dong Won
ABSTRACT: Purpose : To evaluate the incidence of early recurrent hemorrhage in submacular hemorrhage secondary to type 3 neovascularization or retinal angiomatous proliferation (RAP) and its influence on visual prognosis. Methods : This retrospective study included 32 eyes with submacular hemorrhage secondary to type 3 neovascularization or RAP that underwent anti-vascular endothelial growth factor (VEGF) therapy. The eyes exhibiting an increase in the extent of hemorrhage within 6 months after hemorrhage development were included in the early recurrent hemorrhage group, and the remaining eyes were included in the non-early recurrent hemorrhage group. The best-corrected visual acuities (BCVAs) measured at the time of hemorrhage development and at 12 months were compared between the two groups. Results : During the follow-up period, 8 eyes underwent vitrectomy to clear vitreous hemorrhage, and the remaining 24 eyes underwent anti-VEGF monotherapy. In the early recurrent hemorrhage group ( n = 12), the mean logarithm of the minimal angle of resolution BCVA at the time of hemorrhage development and after 12 months was 1.17 ± 0.40 (Snellen equivalents: 20/295) and 2.35 ± 0.59 (20/4477), respectively. In the non-early recurrent hemorrhage group ( n = 20), the corresponding values were 1.07 ± 0.43 (20/234) and 1.44 ± 0.71 (20/550), respectively. The BCVA at 12 months was significantly worse in the early recurrent hemorrhage group ( P = 0.003) despite comparable BCVA at diagnosis between the two groups ( P = 1.000). Conclusions : Early recurrent hemorrhage was noted in 37.5% of eyes with submacular hemorrhage secondary to type 3 neovascularization or RAP and was closely associated with a poor prognosis.